ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN DAN MAKRO EKONOMI TERHADAP BETA SAHAM SYARIAH PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) TAHUN 2006-2013 - Sulestari, Endang; Jati, Agung Nugroho (Kiat Bisnis, 2014)
The purpose of this research is to analyze how the influence of company characteristics and macro economic of net profit margin, current ratio, debt to assets ratio, interest rates, and economic growth of Beta Sharia stocks either simultaneously or partial on companies listed on the Jakarta Islamic Index (JII) during 2006-2013.The data used was secondary data, which was quatitative. This research covered the whole population public companies listed on the Jakarta Islamic Index (JII). Sampling method was using a purposive sampling technique. Data anlysis techniques were using multiple linear analys.The research of hypothesis F-Test, it could be concluded that all the independent variables had significant effects against Beta Sharia stocks. Based on the t-Test, it could be concluded variables that net profit margin, interest rates, and debt to assets ratio influenced in Beta Sharia stocks, meanwhile current ratio and economic growth has no effect againts of Beta Sharia stocks.Â Keywords : sharia stocks beta, net profit margin, current ratio, debt to assets ratio, interest rate, and economic growth.